2016
DOI: 10.1016/j.cobeha.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal exposure to endocrine disruptors: sex, timing and behavioral endpoints

Abstract: Of the approximately 85,000 chemicals in use, 1000 have been identified as having the ability to disrupt normal endocrine function. Exposure to endocrine disrupting chemicals (EDCs) during critical period in brain differentiation (prenatal and neonatal life) via the mother can alter the course of the development of sexually dimorphic behaviors. Bisphenol A (BPA) is a very high volume chemical used in plastic, resins and other products, and virtually everyone examined has detectable BPA. BPA has estrogenic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 60 publications
1
61
1
Order By: Relevance
“…Prior work has demonstrated an impact of BPA (28) and many other EDCs on maternal behavior (55,93,94). Due to differences in study design, timing of treatment, and dosage, it is difficult to compare our study with this seminal work (28).…”
Section: Discussioncontrasting
confidence: 47%
“…Prior work has demonstrated an impact of BPA (28) and many other EDCs on maternal behavior (55,93,94). Due to differences in study design, timing of treatment, and dosage, it is difficult to compare our study with this seminal work (28).…”
Section: Discussioncontrasting
confidence: 47%
“…Among environmental toxicants, endocrine-disrupting chemicals (EDCs) have been associated over these past 50 years with many existing or emerging diseases including hormone-dependent cancers, diabetes, obesity, and decreased fertility (De Coster and van Larebeke, 2012; Maqbool et al, 2016). This is supported by numerous epidemiological surveys (De Coster and van Larebeke, 2012; Grindler et al, 2015; Ehrlich et al, 2016) and experimental studies (Brieño-Enríquez et al, 2015; Chevalier et al, 2015; Robinson and Miller, 2015; Maqbool et al, 2016; Palanza et al, 2016; Ziv-Gal and Flaws, 2016 for recent reviews). Among the thousands of EDCs, bisphenol A (BPA) is one of the most active and ubiquitous due to its wide use by the plastic industry.…”
Section: Introductionmentioning
confidence: 81%
“…Among the thousands of EDCs, bisphenol A (BPA) is one of the most active and ubiquitous due to its wide use by the plastic industry. The consequences of exposure to BPA have been studied in detail in the development and pathophysiology of multiple organs including gonads, brain, pancreas, liver, heart, and adipose tissue, acting on different effectors of the steroid axis (Chevalier et al, 2015; Robinson and Miller, 2015; Palanza et al, 2016; Seachrist et al, 2016; Ziv-Gal and Flaws, 2016 for recent reviews). BPA has also been shown to induce enamel hypomineralization in rats (Jedeon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…exploration, novelty seeking, anxiety) were not statistically significantly altered by perinatal BPA exposure based on an overall analysis, what is observed is that BPA-exposed animals showed no behavioral sex differences while control animals did show the expected significant behavioral sex differences (Gioiosa et al, 2007(Gioiosa et al, , 2013(Gioiosa et al, , 2015Laviola et al, 2005). Several studies have confirmed that specific BPA effects on behaviors can differ across different species or strains of rodents, but the common thread is that exposure to low doses of BPA in utero and early postnatal life disrupts the development of normal sexually dimorphic behaviors, including anxiety, exploration, social interactions, play behavior, reward sensitivity, spatial learning and memory, and sexual and parental behavior, but that this disruption affects males and females differently (reviewed in Palanza et al, 2016). However, explicit recognition of sex differences in performance is not a typical feature of toxicological studies, except for reproductive capacity studies (Weiss, 2011).…”
Section: Sex-dependent Effects Of Developmental Events: the Case Of Ementioning
confidence: 93%